Data to accompany Rigano et. al. (2016) J.Comp.Physiol, B - Rigano, Kimberly S.; Gehring, Jamie L.; Evans Hutzenbiler, Brandon D.; Chen, Annie V.; Nelson, O. Lynne; Vella, Chantal A.; Robbins, Charles T.; Jansen, Heiko T. (Dryad Digital Repository, 2016)
data to accompany manuscript